Air-induced double addition of P(O)–H bonds to alkynes: a clean and practical method for the preparation of 1, 2-bisphosphorylethanes. Issue 6 (31st January 2017) - Guo, Haiqing; Yoshimura, Aya; Chen, Tieqiao; Saga, Yuta; Han, Li-Biao
Abstract : An air-induced double addition of diphenyl phosphine oxide to various alkynes is reported. Abstract : An air-induced double addition of diphenyl phosphine oxide to various alkynes is reported. This reaction can proceed efficiently under metal- and solvent-free conditions, and is a clean and practically useful method for the preparation of the valuable 1, 2-bisphosphorylethanes.